Antioxidative Activity and Phenols Content in Five Tropical Lamiaceae Plants - M. S. Azman, Abdul Rahim; Jailani, Salihon; M. M., Yusoff; M. Rizal, Martua Damanik (UMK Publisher, 2013)
The total antioxidants content in five Lamiaceae plants were examined. Fresh Plecranthus amboinicus Lour. Indonesia leaves were collected from Jakarta, Indonesia and leaves of Plecranthus amboinicus Lour. Malaysia, Pogostemon cablin Benth., Solenostemon scutellariodes Red and Solenostemon scutellariodes Mix Colour were collected from Kuantan, Malaysia. Leaves were freeze-dried, ground and extracted using methanol. The extracted leaves were determined the scavenging activity of the stable 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. Results showed that the P. cablin Benth. leaves exhibited the significant (p<0.05) highest degree of antioxidant activity (63.18%). It was followed by S. scutellariodes Red (54.81%) and S. scutellariodes Mix Colour (50.44%) which both showed significant differences (p<0.05). Both of the P. amboinicus Lour. Malaysia and P. amboinicus Lour. Indonesia displayed the lowest degree of antioxidant activity (p>0.05), i.e 47.07% and 45.38%, respectively. The P. cablin Benth. showed the total phenols (7.64 mg/g fw) but insignificant with the P. amboinicus Lour. Indonesia (7.42 mg/g fw), S. scutellariodes Red (7.32 mg/g fw) and P. amboinicus Lour. Malaysia (7.23 mg/g fw). Only the S. scutellariodes Mix Colour showed significantly (p0.05) compared total phenols (5.64 mg/g fw). This research provided a chemical basis for some of the health benefits claimed for in folk medicine and warrant further studies to develop it as a natural functional food.